Effects of developmental exposure to silver in ionic and nanoparticle form: A study in rats. Issue 1 (December 2016) - Charehsaz, Mohammad; Hougaard, Karin; Sipahi, Hande; Ekici, Asiye; Kaspar, Çiğdem; Culha, Mustafa; Bucurgat, Ülkü; Aydin, Ahmet
Abstract Background Evaluations of silver in both nanoparticle (Ag-NPs) and ionic forms indicate some adverse effects on living organisms, but little is known about their potential for developmental toxicity. In this study, developmental toxicity of Ag-NPs (from 0.2 to 20 mg/kg/day) and ionic Ag (AgNO3, 20 mg Ag/kg/day) were investigated in rats. Methods Animals were dosed by gavage from gestation day 7 − 20. The day after parturition, dams and pups were sacrificed and Ag level assessed in several maternal and pup organs. In addition, hepatotoxicity and oxidative stress parameters and histopathology were evaluated. Results No treatment related effects were found for gestational parameters including pregnancy length, maternal weight gain, implantations, birth weight and litter size at any dose level of Ag-NPs. Maternal weight gain was lower in dams receiving AgNO3 compared to the other groups, suggesting that the ionic form may exert a higher degree of toxicity compared to the NP form. Tissue contents of Ag were higher in all treated groups compared to control dams and pups, indicating transfer of Ag across the placenta. The findings furthermore suggest that Ag may induce oxidative stress in dams and their offspring, although significant induction was only observed after dosing with AgNO3 . Histopathological examination of brain tissue revealed a high incidence of hippocampal sclerosis in dams treated with nanoparticle as well as ionic Ag. Conclusion The difference in offspring deposition patterns between ionic and NP Ag and the observations in dam brain tissue, requires scrutiny, and, if corroborated, indicate that ionic and NP forms maybe need separate risk assessments and that the hazard ratings of silver in both ionic and nanoparticle forms should be increased, respectively. Trial registration Not applicable. Graphical abstract Developmental Toxicity of Ag-NPs.